Ambient wood smoke, traffic pollution and adult asthma prevalence and severity. Issue 7 (23rd September 2013) - Bui, D. Son; Burgess, John A.; Matheson, Melanie C.; Erbas, Bircan; Perret, Jennifer; Morrison, Stephen; Giles, Graham G.; Hopper, John L.; Thomas, Paul S.; Markos, James; Abramson, Michael J.; Walters, E. Haydn; et al.
Abstract Background and objective The impact of ambient wood smoke and traffic‐related air pollution on adult asthma has not been well studied. This paper aims to investigate associations between exposure to ambient wood smoke, traffic‐related air pollution and current asthma/asthma severity in middle age, and whether any associations are modified by atopic status. Methods Using data from the Tasmanian Longitudinal Health Study, associations between ambient wood smoke and two indices of traffic‐related air pollution (frequency of heavy vehicles near the home and frequency of intense traffic noise) and current asthma/asthma severity were investigated. Unconditional logistic regression to examine current asthma and ordinal logistic regression to examine asthma severity was used. Results For asthmatics, both exposure to ambient wood smoke (odds ratio 1.11; 95% confidence interval 1.02–1.20) and being frequently exposed to heavy vehicles (odds ratio 1.80; 95% confidence interval 1.09–2.96) were associated with increased asthma severity. Neither association varied by atopic status. Conclusions In middle‐aged adults, ambient wood smoke and traffic pollution were associated with increased asthma severity. These findings suggest that avoiding or limiting exposure to traffic pollution and wood smoke may help to reduce asthma. Future studies to replicate this finding are recommended and should examine specific biological mechanisms for this effect.